Developing A theoretical model for adoption of facial recognition payment for senior citizens in Tangshan City, Hebei, China - Zhou, Yuhan; Bohari, Abdul Manaf (International Journal of Innovative Research and Scientific Studies, 2025)
Facial recognition payment (FRP) is an emerging biometric authentication technology that enables seamless and contactless transactions. Despite its rapid global adoption, senior citizens in offline settings are often reluctant to embrace FRP due to psychological resistance and technological barriers. This study aims to investigate the key determinants influencing FRP adoption among senior citizens in Tangshan City, Hebei, China. A theoretical model is developed by integrating the Belief-Attitude-Intention (B-A-I) framework with the extended Technology-Organization-Environment-Individual (TOE-I) framework. The model explores the effects of convenience, familiarity, social support, and perceived privacy risk on trust and satisfaction, which subsequently shape the intention to use FRP. Moreover, technology anxiety is examined as a moderating factor that may weaken or strengthen the relationship between trust, satisfaction, and intention to use. This framework provides theoretical insights into digital payment adoption behavior and practical guidance for policymakers and service providers aiming to promote inclusive, age-friendly financial technologies in China and other aging societies.